Serum TRPA1 mediates the association between olfactory function and cognitive function - Liang, Xiaoniu; Xiao, Zhenxu; Wu, Jie; Ma, Xiaoxi; Zhao, Qianhua; Ding, Ding (Frontiers in Aging Neuroscience, 2024)
Olfactory dysfunction was associated with poorer cognition. However, the association between transient receptor potential cation channel subfamily A member 1 (TRPA1) and cognitive function have not been studied. This study aimed to evaluate the mediation effect of TRPA1 on the association between olfactory and cognitive function among Chinese older adults.We recruited 121 participants with cognitive impairment (CI) and 135 participants with normal cognition (NC) from a memory clinic and the "Shanghai Aging Study". Olfactory identification of each participant was measured by the Sniffin' Sticks Screening Test 12 (SSST-12). Serum TRPA1 were quantified using the Enzyme-Linked Immunosorbent Assay. The mediation effects of TRPA1 on the association between olfactory function and cognitive function were explored using mediation analysis.The CI group had a significantly higher proportion of the high level of serum TRPA1 (58.7%) than the NC group (42.2%) (P = 0.0086). After adjusted for gender, age, and years of education, mediation analysis verified that TRPA1 partially mediated the association between . It also verified that TRPA1 partially mediated the association between the identification of peppermint and MMSE.Our study emphasizes the mediation role of TRPA1 in the relationship between olfactory and cognitive function among older adults. Further research is necessary to explore the mechanism of TRPA1 on the relationship between olfactory and cognitive decline.